Solution of Kompaneets equation for shock front in the medium with spherical density stratification - Donets, G.V. (Вопросы атомной науки и техники, 2015)
Based on the solution of the Kompaneets equation for the shock front in a plane-stratified medium with density changing as the hyperbolic tangent, an exact solution for the off-center explosion in a medium with a spherical stratification is obtained. Solutions connected by logarithmic transformation, which allows to build SF in all regions and investigate its evolution. На основі рішення рівняння Компанійця для ударного фронту (УФ) в площинно-стратифікованому середовищі для щільності, що змінюється за законом гіперболічного тангенса, отримано точне рішення для нецентрального вибуху в середовищі зі сферичною стратифікацією. Рішення пов'язані логарифмічним перетворенням, що дозволяє побудувати УФ у всіх областях і досліджувати його еволюцію. На основании решения уравнения Компанейца для ударного фронта (УФ) в плоско-слоистой среде для плотности, изменяющейся по закону гиперболического тангенса, получено точное решение для нецентрального взрыва в среде со сферической стратификацией. Решения связаны логарифмическим преобразованием, позволяющим построить УФ во всех областях и исследовать его эволюцию.